The relationship between service guarantees, empowerment, employee satisfaction, service quality in four and five star hotels in Malaysia - Mohd Shahril, Aslinda; Abdul Aziz, Yuhanis; Othman, Mohhidin; Bojei, Jamil (IACSIT Press, 2013)
Despite the numerous benefits of the implementation of service guarantees in service organizations, there is a dearth of studies that explore the relationship between service guarantees, empowerment, employee satisfaction and service quality, particularly in the hotel industry. The aim of the study is to examine the relationship between service guarantees and employee empowerment and to investigate the correlation between empowerment and employee satisfaction and establish its links to service quality. This study employed the quantitative methodology based on survey questionnaires distributed to frontline employees in various four and five star hotels in Malaysia. The empirical findings provide evidence that service guarantees have a positive relationship with empowerment. However, the study found that empowerment has an insignificant relationship with employee satisfaction. Notably, it was found that employee satisfaction has a significant relationship with service quality. The study’s limitations and suggestions for future research are discussed.